Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1017/s000711451000423x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of salt intake by 24 h urinary sodium excretion in a representative sample of Spanish adults

Abstract: The present study reports the Na intake of a representative sample of Spanish young and middle-aged adults aged 18-60 years (n 418, 53·1 % women, selected from the capitals of fifteen provinces and the surrounding semi-urban/rural area), measured with a 24 h urinary Na excretion method. To validate the paper collection of 24 h urine, the correlation between fat-free mass determined by electrical bioimpedance (50·8 (SD 11·3) kg) and that determined via urinary creatinine excretion (51·5 (SD 18·8) kg) was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
5
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 33 publications
10
72
5
12
Order By: Relevance
“…As another study [21], we found that Na + and K + excretions were higher in men than in women, which confirms observations in other countries [22,23], that the intake of sodium is higher than the daily recommendations while potassium is below them, 2 g and 3.51 g, respectively [17,24].…”
Section: Discussionsupporting
confidence: 90%
“…As another study [21], we found that Na + and K + excretions were higher in men than in women, which confirms observations in other countries [22,23], that the intake of sodium is higher than the daily recommendations while potassium is below them, 2 g and 3.51 g, respectively [17,24].…”
Section: Discussionsupporting
confidence: 90%
“…Other authors mention values of between usually maintain the organoleptic and nutritional characteristics of the mixture used (Wang et al 2010). In Spain, 88.2 % of the population ingests 9.8 g/day of sodium, which is above the recommended amount of 5 g/ day (Ortega et al 2011). A moderate decrease in salt intake (only 10 %) would contribute to reducing strokes and heart attacks, as well as the risk of cardiovascular pathologies (He and MacGregor 2011).…”
Section: Discussionmentioning
confidence: 99%
“…First, the use of an opportunistic sampling frame may introduce a bias in the overall estimate of salt consumption, affecting the validity of the survey. 24h urine collections often are a burden to participants of large population-based dietary surveys so that, despite great efforts and resources, response rates are often low [15,30,39,40]. A recent study has compared the results of an opportunistically recruited volunteer population sample where a random sampling had yielded a 16% response rate [15].…”
Section: Limitations Of the Studymentioning
confidence: 99%